Black earth wisdom : soulful conversations with Black environmentalists - Penniman, Leah (Amistad, an imprint of HarperCollinsPublishers, 2023)
"A soulful collection of illuminating essays and interviews that explore Black people's spiritual and scientific connection to the land, waters, and climate, curated by the acclaimed author of Farming While Black"--